Diabetic retinopathy as a potential marker of Parkinson's disease: a register-based cohort study. Issue 4 (8th November 2021) - Larsen, Maria E C; Thykjaer, Anne S; Pedersen, Frederik N; Möller, Sören; Laugesen, Caroline S; Andersen, Nis; Andresen, Jens; Hajari, Javad; Heegaard, Steffen; Højlund, Kurt; Kawasaki, Ryo; Schielke, Katja C; et al.
Abstract: Neurodegeneration is an early event in the pathogenesis of diabetic retinopathy, and an association between diabetic retinopathy and Parkinson's disease has been proposed. In this nationwide register-based cohort study, we investigated the prevalence and incidence of Parkinson's disease among patients screened for diabetic retinopathy in a Danish population-based cohort. Cases ( n  = 173 568) above 50 years of age with diabetes included in the Danish Registry of Diabetic Retinopathy between 2013 and 2018 were matched 1:5 by gender and birth year with a control population without diabetes ( n  = 843 781). At index date, the prevalence of Parkinson's disease was compared between cases and controls. To assess the longitudinal relationship between diabetic retinopathy and Parkinson's disease, a multivariable Cox proportional hazard model was estimated. The prevalence of Parkinson's disease was 0.28% and 0.44% among cases and controls, respectively. While diabetic retinopathy was not associated with present (adjusted odds ratio 0.93, 95% confidence interval 0.72–1.21) or incident Parkinson's disease (adjusted hazard ratio 0.77, 95% confidence interval 0.56–1.05), cases with diabetes were in general less likely to have or to develop Parkinson's disease compared to controls without diabetes (adjusted odds ratio 0.79, 95% confidence interval 0.71–0.87 and adjusted hazard ratio 0.88, 95% confidence interval 0.78–1.00). In a national cohort of more than 1 million persons, patients with diabetes were 21% and 12% were less likely to have prevalent and develop incident Parkinson's disease, respectively, compared to an age- and gender-matched control population without diabetes. We found no indication for diabetic retinopathy as an independent risk factor for incident Parkinson's disease. Abstract : In this register-based cohort study investigating the association between diabetic retinopathy and Parkinson's disease, Larsen et al. report that diabetic retinopathy does not increase the risk of having or developing Parkinson's disease; on the contrary, diabetes per se seems to have a protective effect. Graphical Abstract: